The Effect of Text Medium on the Reading Profiles of College-Aged Individuals - McNeil, Brianna T.; Sellers, Lynsey B. (My University, 2020)
Department of Communication Sciences and Disorders and Special Education Numerous studies have been designed to compare the comprehension abilities of readers when reading digital texts as opposed to print-based texts. Although participants have reported preferring the digital medium, studies tend to show that individuals comprehend with greater depth when interacting with hard-copy texts. However, comprehension is a construct that is extremely difficult to measure given its multifaceted nature. There is no accepted practice when it comes to assessing comprehension since minor deviations between assessment procedures can yield dramatically differing results. As such, the assessment of lower-level abilities often receives preeminent status since these measures tend to exhibit higher levels of construct validity, yet no current studies have examined the effects of medium on these lower-level abilities. The current study sought to examine the effects of utilizing digital mediums on the lower-level reading abilities of college-aged participants. Each participant completed a series of counter-balanced oral reading tasks that varied as a function of medium (digital vs. print). Measures of reading accuracy, reading rate, and reading fluency were obtained in addition to measures of comprehension. Results were interpreted in terms of their academic ramifications.